The Implementation of the Employment Social Security Program for Non-Wage Workers in the Semarang City Region in View from the Minister of Manpower Regulation number 1 of 2016 - Luhur Sanitya Pambudi (Universitas Negeri Semarang, 2019)
The purpose of this study is to evaluate the implementation of the employment social security program for non-wage workers in the Semarang area. This study uses a qualitative approach to the type of sociological juridical research. Research data sources are primary and secondary data. Data collection techniques: interviews with the Head of Marketing of the BPU Kancab BPJS Employment Semarang I, Semarang City DPRD Members and Workers who are not wage earners, as well as making observations, and documentation or literature studies. Data validity uses source triangulation with data analysis carried out inductively. Based on the research results obtained, the implementation of the social security program for non-wage workers in the Semarang area has adjusted the Minister of labor Regulation No. 1 of 2016 concerning the Procedures for Implementing Work Accident Insurance, Death Guarantee, and Old Age Insurance for Non-Participants Wage Recipients, it's just that there are breakthroughs outside the regulations set by the BPJS Employment to facilitate participants in getting benefits from the employment social security program, namely payment of flexible fees. Also, some factors become a factor of donors, including easy registration of participants, payment of low contributions, and there is no ceiling limit for medical services in the event of a work accident. Then the inhibiting factors are the lack of awareness of workers in the informal sector, the age limit of being a participant at 56 years, and the low level of the economy. So there needs to be attention from the Government and the Legislature to support the membership of BPJS Employment for non-wage workers.